A rare pulmonary lymphangioleiomyomatosis disease in a male with tuberous sclerosis complex. (2020) - Kabi, Ankita; Panda, Sagarika; Sama, Sonu; Kumar, Subodh; Kaeley, Nidhi; Sogal P, Sachin
Abstract: Background: Pulmonary Lymphangioleiomyomatosis (LAM) is an uncommon disease and may be associated with tuberous sclerosis complex (TSC). LAM is reported to occur exclusively in females of the premenopausal age group. Here we report a rare entity of lymphangioleiomyomatosis in a male patient of tuberous sclerosis, who developed pneumothorax following mechanical ventilation. Case summary: A young adult presented to the emergency room with history of recurrent seizures since the 6th month of his age. He was intubated in the emergency room for protection of the airway and was initially maintained on manual ventilation using Bain's circuit. Neuroimaging revealed multiple calcified subcortical nodules and giant cell astrocytoma in left lateral ventricle. On the third day of hospitalization, he developed subcutaneous emphysema on his neck and anterior wall of chest. Contrast-enhanced CT chest revealed presence of subcentimetric thin walled cystic lesions in lungs, pneumomediastinum, right sided pneumothorax, and diffuse subcutaneous emphysema. Right sided pneumothorax was managed by intercostal chest tube drainage. CECT abdomen showed well defined heterogeneously enhancing lesions in right kidney suggestive of angiomyolipoma. A final diagnosis of Lymphangioleiomyomatosis (LAM) in tuberous sclerosis (TSC) was made. Considering the high recurrence of pneumothorax, pleurodesis was done and sirolimus (2 mg per oral OD) was initiated. Conclusion: Cystic lung disease consistent with LAM is a rare entity in males with TSC, which can be missed easily in patients with extra-pulmonary manifestations. Treating clinician or intensivist should remain vigilant. Active follow-up, chest imaging and pulmonary function testing should be advised to screen the patients for coincidental finding of LAM.